Merawat Toleransi: Dinamika Hubungan Antaragama di Dunia Melayu Kontemporer: Dinamika Hubungan Antaragama di Dunia Melayu Kontemporer - Mhd Luthfi Alhamidi; Salsabila Dwi Putri (SUARGA: Studi Keberagamaan dan Keberagaman, 2025)
Malay is actually similar to a nation or a group of ethnic groups that adhere to the same religion and use the same language. Then there were also foreign descendants such as Arab, Persian, Chinese and Indian in addition to descendants from other Nusantara techniques. Where in one nation does not only consist of one religion. This manuscript was written using the concept of historical research to see the dynamics of Islam in the Malay world to examine and maintain tolerance between religions. To examine and maintain tolerance for religion in the Malay region, the right theory to study it is the response and challenge theory from Arnold Toyenbe which states that every historical movement arises because of a stimulus so that a reaction appears that gives birth to change. The result of this discussion is that in the contemporary era, the Malay period faces various challenges and they must respond quickly so that they are not left behind. Proven by the existence of driving organizations as a place to express aspirations/opinions.